Peningkatan Minat Belajar Siswa Melalui Media Belajar Berbasis Teknologi Gamifikasi Pada Pembelajaran Bahasa Indonesia di Kelas 9 di SMP Negeri 13 Surabaya - Ocarina Alya Indraswari (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
The research conducted in this proposal aims to determine and analyze the use of gamification technology media in increasing the learning interest of students in class 9 D SMPN 13 Surabaya. This research is designed with qualitative methods and uses data collection techniques in the form of filling out student interest observation sheets in the learning process. The results of filling out student observations are expected to be used as evaluation material in the classroom learning process. Thus, it is hoped that the results of this study can be useful as a reference for educators to develop teaching media that will be used in the learning process in the classroom. Various rapidly developing technologies must of course be utilized properly, so that later the educational process in the classroom is not left behind by existing technological developments. Nowadays, there are many websites or applications that can help the learning process in the classroom. The idea of student-centered education should make educators no longer use the lecture method when explaining in the learning process. This is what makes educators clever in utilizing various learning resources and media including technology. In the meaning of KBBI technology is a scientific method that can be used as a means to provide various things needed for the continuity and comfort of human life to make it more practical.